(untitled) (Herald of the National Children’s Medical Center, 2024)
Abstract: This article is devoted to the issues of integral assessment of the condition and prediction of outcomes of children with critical shock conditions at the prehospital stage of emergency medical care. Materials and methods of research: Data from the medical history of 895 children were retrospectively studied and 143 children aged 12 to 18 years old with critical shock who were admitted by ambulance in Tashkent were selected from them. Results of the study: A comparative analysis of the statistical parameters of the variables of the integral scales was carried out to determine the diagnostic effectiveness. It has been established that integral scales for assessing the severity of patients’ condition can be used in patients with critical shock conditions, both for individual prognosis of the outcome of the disease and in evaluating the effectiveness of intensive care at the stages of treatment. Conclusion: The use of a score assessment of only the respiratory, cardiovascular and renal systems on integral scales can find practical application in assessing the individual prognosis of outcome in patients with critical shock.